Effect of Ductility Level on the Seismic Behavior of Low Reinforced Concrete Moment-Resisting Frames Equipped by Double Friction Pendulum Bearings Isolation - Seyed Ali Razavian Amrei; Seyed Amirhossein Ahmadi; Ayoub Shakouri; Gholamreza Ghodrati Amiri; Elham Rajabi (Journal of Rehabilitation in Civil Engineering)
The base isolation method is being utilized for more than two decades as a way to protect structures. Despite recent advancements in the seismic evaluation of isolated structures, the impact of ductility level on based-isolated Reinforced Concrete (RC) moment-resisting frame structures has not been explored. In order to consider the effect of ductility level, the present paper evaluates the seismic behavior of isolated RC moment-resisting frames through Double Friction Pendulum Bearings (DFPB) with ordinary, intermediate, and special ductility. Additionally, we compared responses of these systems with the similar conventional structures. To this end, three RC moment-resisting frame structures were designed with/without DFPB, and three-dimensional (3D) models were implemented in OpenSees. Then, seismic responses of these six models, including peak floor absolute acceleration, base shear, plastic rotation, and story drift of column were evaluated. According to the results. Ductility levels have a significant impact on the fixed and isolated structures. As a result of the special moment-resisting frame superstructure, plastic rotation and peak drift demand of columns is increased compared to the ordinary and intermediate ones. The maximum differences in plastic rotation and peak drift demand between ordinary and special frames were obtained as approximately 70% and 50% in base-isolated buildings.